First-principles study of a MXene terahertz detector. Issue 1 (1st December 2017) - Jhon, Y. I.; Seo, M.; Jhon, Y. M.
Abstract : MXenes can serve as excellent terahertz detecting materials regardless of the stacking and/or the presence of interlayer water molecules. Abstract : 2D transition metal carbides, nitrides, and carbonitrides called MXenes have attracted increasing attention due to their outstanding properties in many fields. By performing systematic density functional theory calculations, here we show that MXenes can serve as excellent terahertz detecting materials. Giant optical absorption and extinction coefficients are observed in the terahertz range in the most popular MXene, namely, Ti3 C2, which is regardless of the stacking degree. Various other optical properties have been investigated as well in the terahertz range for in-depth understanding of its optical response. We find that the thermoelectric figure of merit ( ZT ) of stacked Ti3 C2 flakes is comparable to that of carbon nanotube films. Based on excellent terahertz absorption and decent thermoelectric efficiency in MXenes, we finally suggest the promise of MXenes in terahertz detection applications, which includes terahertz bolometers and photothermoelectric detectors. Possible ZT improvements are discussed in large-scale MXene flake films and/or MXene–polymer composite films.